Pengaruh Thin Capitalization, Konservatisme Akuntansi Dan Financial Distress Terhadap Penghindaran Pajak Dengan Kepemilikan Institusional Sebagai Moderasi - Nur Nilam Sari; Sekar Mayangsari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the effect of thin capitalization, accounting conservatism and financial distress on tax avoidance with institutional ownership as moderating. This study uses secondary data, the data used in the form of financial report and annual report of companies listed on the Indonesia Stock Exchange. The type of research used in this study is causal research, namely research that aims to find a causal relationship of the variables studied to answer research questions. The samples used in this study are property and real estate companies that are listed on the Indonesia Stock Exchange in the period of 2018-2022. Data were collected using purposive sampling. The total number of companies in the study sample is 92 companies with a study period of 5 years, resulting in 80 samples after outliers. The results of the study using linear regression analysis, descriptive statistic, classic assumption and moderating regression analysis test indicate that thin capitalization and financial distress has a significant positive effect on tax avoidance. Furthermore, the results of linear regression analysis indicate that accounting conservatism not effect on tax avoidance. Then the results of moderating regression analysis test indicate that institutional ownership can strengthen the influence of thin capitalization, accounting conservatism and financial distress on tax avoidance. Keywords: Thin Capitalization, Accounting Conservatism, Financial Distress, Institutional Ownership, Tax Avoidance